Comparison of performance of the 2016 ACR-EULAR classification criteria for primary Sjögren's syndrome with other sets of criteria in Japanese patients. Issue 12 (22nd March 2017) - Tsuboi, Hiroto; Hagiwara, Shinya; Asashima, Hiromitsu; Takahashi, Hiroyuki; Hirota, Tomoya; Noma, Hisashi; Umehara, Hisanori; Kawakami, Atsushi; Nakamura, Hideki; Sano, Hajime; Tsubota, Kazuo; Ogawa, Yoko; et al.
Abstract : Objectives: To compare the performance of the new 2016 American College of Rheumatology (ACR)-European League Against Rheumatism (EULAR) classification criteria for primary Sjögren's syndrome (SS) with 1999 revised Japanese Ministry of Health criteria for diagnosis of SS (JPN), 2002 American-European Consensus Group classification criteria for SS (AECG) and 2012 ACR classification criteria for SS (ACR) in Japanese patients. Methods: The study subjects were 499 patients with primary SS (pSS) or suspected pSS who were followed up in June 2012 at 10 hospitals in Japan. All patients had been assessed for all four criteria of JPN (pathology, oral, ocular, anti-SS-A/SS-B antibodies). The clinical diagnosis by the physician in charge was set as the 'gold standard'. Results: pSS was diagnosed in 302 patients and ruled out in 197 patients by the physician in charge. The sensitivity of the ACR-EULAR criteria in the diagnosis of pSS (95.4%) was higher than those of the JPN, AECG and ACR (82.1%, 89.4% and 79.1%, respectively), while the specificity of the ACR-EULAR (72.1%) was lower than those of the three sets (90.9%, 84.3% and 84.8%, respectively). The differences of sensitivities and specificities between the ACR-EULAR and other three sets of criteria were statistically significant (p<0.001). Eight out of 302 patients with pSS and 11 cases out of 197 non-pSS cases satisfied only the ACR-EULAR criteria, compared with none of the other three sets. Conclusions: The ACR-EULAR criteria had significantly higher sensitivity and lower specificity in diagnosis of pSS, compared with the currently available three sets of criteria.